STRATEGI KOMUNIKASI TVONE DALAM PENAYANGAN MAKELAR KASUS PALSU - Yuniarti, Tatik (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
This article discusses an example the case a broker of a major media company that is TVOne. A private television station in Indonesia is experiencing problems related to the credibility of the election of a resource person in the show. Problems occur when one a journalist of TVOne displays case a broker in the body of the Indonesian Police Headquarters (Police Headquarters) in the program Apa Kabar Indonesia Pagi, on March 18, 2010. The program was to discuss the hot topics by displaying a competent resource persons. Incidentally when the topics discussed, the public was case a broker highlighted the discovery of cases of tax at the Directorate General of Taxation. But in that program, presented by resource persons found not credible. This is because the testimony presented regarding the existence of a case a broker at Police Headquarters body was counterfeit. Resource persons named Andris Ronaldi told presenter confessed TVOne, Indi Rahmawati pretend to be a case a broker at Police Headquarters. Based on these cases, in this article will discuss how a major television station as a trusted community of reference television news maintained its reputation after the case occurred. As a television station that has not been long standing, TVOne is building the image into news television station in Indonesia